2013
DOI: 10.1007/s10120-013-0254-x
|View full text |Cite
|
Sign up to set email alerts
|

Gastric cancer stem cells: therapeutic targets

Abstract: During the past decade, a growing body of evidence has implied that cancer stem cells (CSCs) play an important role in the development of gastric cancer (GC). The notion that CSCs give rise to GC and may be responsible for invasion, metastasis, and resistance to treatment has profound implications for anti-cancer therapy. Recent major advances in the rapidly evolving field of CSCs have opened novel exciting opportunities for developing CSC-targeted therapies. Discovery of specific markers and signaling pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 138 publications
(203 reference statements)
0
48
0
1
Order By: Relevance
“…For instance, myofibroblasts expressing a high level of hepatocyte growth factor can activate Wnt signaling and even restore the stem cell phenotype in more differentiated tumor cells [38]. The Hedgehog and Notch pathways are also known to be deeply involved in the cancer stem cell properties [4]. Thus, our results suggest that LGR5 overexpression alone is not sufficient to recapitulate the molecular characteristics of LGR5-positive cells in GC.…”
Section: Snu484mentioning
confidence: 38%
See 1 more Smart Citation
“…For instance, myofibroblasts expressing a high level of hepatocyte growth factor can activate Wnt signaling and even restore the stem cell phenotype in more differentiated tumor cells [38]. The Hedgehog and Notch pathways are also known to be deeply involved in the cancer stem cell properties [4]. Thus, our results suggest that LGR5 overexpression alone is not sufficient to recapitulate the molecular characteristics of LGR5-positive cells in GC.…”
Section: Snu484mentioning
confidence: 38%
“…Rapidly mounting evidence suggests that cancer stem cells not only maintain tumor growth but also result in relapse after therapy, suggesting they could be a candidate for new targeted therapy [4]. Leucine-rich-repeat-containing G-protein-coupled receptor 5 (LGR5) has been demonstrated as a global stem cell marker in multiple organs, including the small intestine, colon, stomach, hair follicle, kidney, ovary, liver, and mammary gland [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Tumor cells have heterogeneity and the less-differentiated CSCs are recognized as the origin of tumorigenesis, metastasis and recurrence in numerous human cancers1632. Gastric CSCs have been isolated in several cell lines as well as in primary tumors1933. Our results showed that CDDP elevated the ratios of SP and CD44 + /EpCAM + cells in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 59%
“…There are mainly three methods for the identification of CSCs or CSC-like properties: (1) use of CSCs surface markers, such as CD44 + CD24 − , CD133, CD44 + /EpCAM + , and CD901718; (2) identifying the side population (SP) in cancer cells, which enriches CSC-like properties; and (3) determining the growth properties of cells in serum-free suspension culture19. Here, in GC cells, we validated that, CDDP elevated the ratios of SP and CD44 + /EpCAM + cells in a dose-dependent manner (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Transforming growth factor  (TGF-), Wnt and hedgehog signaling are pivotal pathways that influence the cell division, invasion, migration and ulcer repair processes Lagasse, 2008;Zhao, 2014). Disorders in these processes usually lead to gastric adenocarcinoma and other tissue-specific gastrointestinal cancers (Stojnev et al, 2014). Genome sequencing and comprehensive molecular profiling have identified novel driver mutations involved in stem cell pathways in gastric cancer.…”
Section: Stem Cell Pathwaysmentioning
confidence: 99%